Mapping the pH and salinity values for paddy field area in East Coast Malaysia using kriging interpolation technique / Nor Fakira Alia Mohd Rapi, Nur Asma Amirah Mohd Asri and Maizura Mohd Sani - Mohd Rapi, Nor Fakira Alia; Mohd Asri, Nur Asma Amirah; Mohd Sani, Maizura (UiTM Press, 2021)
In paddy farming, the condition of soil is one of the important factors to promote a healthy growing plant. Certain pH and salinity levels are required in order to have soil condition which suits the microorganism life and promotes nutrient opportunity to the plant. Currently, the method used to identify the pH and salinity levels of the soil is by embedding a sensor on the soil which requires cost and time. Furthermore, it will only show the pH and salinity values at only one point and there are limitations if the area of interest is difficult to be accessed. In this research, a method was studied by using Kriging interpolation technique to map soil salinity and pH near Kelantan and Terengganu paddy cultivation area. Ground truth data were pre-processed to generate an image model mapping which consists of acidity, neutral, alkalinity and level of salinity at coordinates of interest using ArcGIS Pro software. As a result, the estimated pH and salinity value range were between 3.9 to 5.9 and 0.48 to 0.71 ds m1 respectively. To test the accuracy of the model, analysis of RMSE was done for pH (0.854) and salinity (0.057). This research shall contribute as a preliminary study to model the soil pH and salinity values for monitoring purpose and as an aid to the farmers.